2022
DOI: 10.1021/acs.jafc.1c06838
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Plant Transfer Rates of Seven Fluorotelomer Precursors to Perfluoroalkyl Acids and F-53B in a Soil-Plant System with Maize (Zea mays L.)

Abstract: Fluorotelomer precursors in soil constitute a reservoir for perfluoroalkyl acids (PFAAs) in the environment. In the present study, precursor degradation and transfer rates of seven fluorotelomer precursors and F-53B (chlorinated polyfluoroalkyl ether sulfonates) were investigated in pot experiments with maize plants (Zea mays L.). The degradation of fluorotelomer precursors to perfluoroalkyl carboxylic acids (PFCAs) and their uptake spectra corresponded to those of fluorotelomer alcohol (FTOH) in terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Hence, it is highly plausible that the observed long-term leaching at t > 600 d in the lysimeter is attributable to the transformation of PFOA precursors, such as 8:2 diPAP. This is consistent with Guelfo et al ( 2020 ), who stated that precursor transformation may be more important than rate-limited leaching at field scale, and other studies (Röhler et al 2021 ; Schaefer et al 2022a ; Just et al 2022 ).…”
Section: Resultssupporting
confidence: 90%
“…Hence, it is highly plausible that the observed long-term leaching at t > 600 d in the lysimeter is attributable to the transformation of PFOA precursors, such as 8:2 diPAP. This is consistent with Guelfo et al ( 2020 ), who stated that precursor transformation may be more important than rate-limited leaching at field scale, and other studies (Röhler et al 2021 ; Schaefer et al 2022a ; Just et al 2022 ).…”
Section: Resultssupporting
confidence: 90%
“…Hence, the high PFAS concentrations in the plant make up less than 0.1% of the overall detected PFAS mass and consequently only have a small influence on the total PFAS balance. A similar result was found by Just et al 30 for the uptake of 6:2 diPAP degradation products into maize plants with a recovery rate of 1.4% of the initially applied PFAS amount in the aboveground plant compartments.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…Atmospheric deposition is assumed to be negligible, as no PFAS were detected in the system compartments (soil, leachate, and grass) of the control variant. Studies by Bizkarguenaga et al 33 and Just et al 30 demonstrated evidence of minimal diPAP uptake into plants. Mass Balance.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, instrumental analysis is performed most commonly using liquid chromatography (LC) coupled with tandem mass spectrometry (MS/MS) (Felizeter et al 2012; or high-resolution mass spectrometry (HRMS) (Just et al 2022). These techniques allow for identifying and quantifying specific PFAS in plant samples, providing insights into their presence and levels in different plant tissues.…”
Section: Pfas Analysis In Plantsmentioning
confidence: 99%